Efektivitas Pembelajaran IPS Kelas IV dengan Menggunakan Multimedia Berbasis Komputer di SDP II Yogyakarta - Budyartati, Sri (Jurnal Pendidikan, 2010)
This research is intended to: 1) identify the effectiveness of computer-based media in teaching Social Science. 2) depict the attraction of computer multimedia in teaching Social Science. This research is carried out under experimental design with pre-test and post-test on Elementary School of Percobaan II, Caturtunggal, Depok, Sleman, Yogyakarta, Fourth Grade, Semetser Two, Term 2007/2008. The subjects of the research consist of 42 students who belong to control class and 44 students who belong to experiment class, who are drawn under random sampling technique. The data drawn by test applied to both groups are analyzed by means of independent t-test to identify the effectiveness of multimedia. To identify the attraction of multimedia the data are drawn under descriptive-quantitative method. Treatment is carried out for the experiment class by making use of storyboard which is validated by 1 expert in multimedia and 1 expert of teaching materials. The implementation is carried out on 6 students of small group and 36 students of large group.The analysis shows a significant different of achievement between control and experiment classes. The counted t (by 6.5) is higher than the table t (by 2.39) under 0.000 < 0.01 of significance value for df (degree of freedom) of 84. Ho is then disapproved indicating that there is significant different of the studentsâ achievement under both classes. The overall attraction of multimedia is tentatively high, with the average score of 4.2 (at 1-5 scale) out of 22 indicators measuring graphic, animation, video, colour, letters, backing music.Key words:Â Â Â Â Â Â Â Â Â effectiveness, teaching Social Science, computer-based multimedia.